Nodal Solutions to Quasilinear Elliptic Problems Involving the 1-Laplacian Operator via Variational and Approximation Methods - Figueiredo, Giovany M.; Pimenta, Marcos T.O. [UNESP] (Indiana University, 2022)
In this work we use two different methods to get nodal solutions to quasilinear elliptic problems involving the 1-Laplacian operator. In the first one, we develop an approach based on a minimization of the energy functional associated with a problem involving the 1-Laplacian operator in RN, on a subset of the Nehari set which contains just sign-changing functions. In the second part we obtain a nodal solution to a quasilinear elliptic problem involving the 1-Laplacian operator in a bounded domain, through a thorough analysis of the sequence of solutions of the p-Laplacian problem associated with it, as p → 1+. In both cases, several technical difficulties appear in comparison with the related results involving signed solutions.
Keywords: 1-Laplacian operator; Nehari method; nodal solutions